Handbook of global contemporary Christianity : movements, institutions, and allegiance - Hunt, Stephen, 1954- (Brill Handbooks on Contemporary Religion, 2016)
The Handbook of Contemporary Christianity: Movements, Institutions andamp; Allegiance traces how the largest religion in the world continues to be expressed in energetic global dynamic forms. In contemporary times Christianity is increasingly exposed to divisions, not only through its traditional channels - Roman Catholic, Protestant and the Orthodoxy - nor conservative and liberal streams, but numerous nuanced articulations. This is reflected in the roles of clergy and lay people, in organisational dynamics, sources of allegiance and articulations of the faith, movements of renewal and revivalism, syncretic modes, and broader relationships with wider cultural trajectories and changing social circumstances. Collectively the contributors to this volume offer a comprehensive exploration of these themes. The volume is a companion to the Handbook of Global Contemporary Christianity.